The Predictors Of Self Empowerment On Type 2 Diabetes Mellitus Among Indonesian - Ratna Wirawati Rosyida; Muhammad G A Putra; Winda Rofiyati; Tengku Isni Yuli (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Self empowerment as the important factor which support diabetes management effectively. Self empowerment describes how diabetic patients perform problem solving and decision taking in diabetes self management. Diabetic patients with self empowerment in higher score will have good effect on quality of life, glycemic control, and prevention of long-term complication. To identify predicting factors of self empowerment on type 2 diabetes mellitus among Indonesian. A cross sectional study was conducted to 77 respondents with type 2 diabetes mellitus and registered as patients in primary health center. Respondent’s characteristic questionnaire included age, gender, occupation, level of education, family support, history of diabetes education and Diabetes Empowerment Scale- Short Form were distributed to responden. Data were analysed using linier regression. The mean age of respondents were 56,9±8,05 years, 55,8% were female, 33,8% were senior high school, 51,9% were in office, 66,2% had family support, 41,6% with history of diabetes education, and mean of self empowerment were 23,25±6,51. The predictors of self empowerment were level of education (β=0,22;p=0,045) and family support (β=0,29;p=0,008) with positive correlation. These factors predicted 12,3% of self empowerment. Level of education affects the capability to get information. Family support create the valuable feeling and positive view of life. These current result reflect the previous findings. Level of education and family support contributed to predict self empowerment in type 2 diabetes mellitus among Indonesian. The higher the level of education, the higher the self empowerment score and the attendance of family support increased the self empowerment score.